A superb solo, or a deviant duet? Overlapping songs in superb fairy-wrens. (16th April 2019) - Taylor, Claire J; Hall, Michelle L; Cain, Kristal E; Langmore, Naomi E
Abstract: Avian duets are formed when 2 birds coordinate their songs. Most research on the evolution and function of duetting has focused on species with highly coordinated duets, and less is known about the context and function of overlapping songs that are more loosely coordinated, in part due to the challenge of determining whether such vocalizations coincide by chance or through coordination between the partners. Here, we use field recordings and playback experiments to test whether breeding pairs of superb fairy-wrens, Malurus cyaneus, coordinate their territorial songs to form duets. We test 3 key characteristics of duetting; whether partners' songs 1) overlap more than expected by chance; 2) have a stereotyped structure that occurs repeatedly and predictably in time, and 3) show evidence of a constant time lag between the contributions of the 2 participants, indicating that individuals are coordinating their songs. This is the first study to quantify the temporal precision of song between partners to investigate coordination in the Malurus genus, an important model taxon for song, sexual selection, and speciation. We found variation in the extent to which partners' songs overlapped, with some individuals overlapping their partners' songs more than expected by chance, no difference in structure of solo and overlapping songs, and no evidence of a consistent response interval. Thus song overlap in superb fairy-wrens meets only some criteria for duetting. We suggest that overlapping songs in this species may be due to individuals responding independently of the same stimulus and/or "call and answer" between pair members. Abstract : There is more to a duet than simply singing together. Bird song may overlap by design, by chance, or because individuals respond independently of the same stimulus. The overlap of superb fairy-wren songs only meets some of the criteria from the current definitions of duets. Species with less-coordinated song allow us to explore the grey area between duets and chance song overlap, and begin to distill traits important for duet evolution and maintenance.